Clinical Stroke Penumbra: Use of National Institutes of Health Stroke Scale as a Surrogate for CT Perfusion in Patient Triage for Intra-Arterial Middle Cerebral Artery Stroke Therapy - Boxerman, J.L. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: CTP may help triage acute stroke patients for IAT, but requires additional contrast agent, radiation, and imaging time. Our aim was to determine whether clinical examination (NIHSS) with NCCT and CTA can substitute for CTP without significantly affecting IAT triage of patients with acute MCA stroke. MATERIALS AND METHODS: We reviewed NCCT, CTA, and CTP imaging performed within 8 hours of symptom onset in 36 patients presenting with MCA territory stroke (September 2007–October 2009). Two neuroradiologists reviewed, independently and by consensus, NCCT, CTA, and CTP (CTP group), and 2 different neuroradiologists blinded to CTP reviewed NCCT, CTA, and NIHSS (stroke scale group) to determine IAT eligibility: M1 or proximal M2 occlusion; infarct core <1/3 MCA territory; and ischemic penumbra >20% infarct core. The stroke scale group estimated infarct core from NCCT and CTA source images and ischemic penumbra from core size relative to NIHSS score and re-evaluated patients after unblinding to CTP. We computed intragroup and intergroup κ scores for IAT treatment recommendation and used the McNemar test to determine whether CTP significantly affected the stroke scale group's decisions. RESULTS: IAT was recommended in 16/36 (44%) and 17/36 (47%) patients by the CTP and stroke scale groups, respectively, with intragroup κ scores of 0.78 ± 0.11 versus 0.83 ± 0.09. The intergroup κ score was 0.83 ± 0.09. When unblinded to CTP, the stroke scale group revised 2/36 (5.6%) decisions, which was insignificant (P = .48, McNemar test). CONCLUSIONS: NIHSS interpreted with NCCT and CTA may be an effective substitute for CTP-derived measures in the IAT triage of patients with acute MCA stroke. Replacing CTP may potentially reduce radiation and contrast dose and time to treatment.